Communicative Tolerance of Policemen in the Context of Their Emotional Intelligence’ Study - O. О. Yevdokimova; Y. S. Ponomarenko (Law and Safety)
This paper presents the results of an empirical study of the peculiarities of manifestations of emotional intelligence among police officers with different levels of communicative tolerance at the stage of primary vocational training. In this context, the actual model of emotional intelligence and its practical application need to be verified taking into account the specifics of police activity. Emotional intelligence is considered primarily as an integral feature of the personality of a policeman in the context of his professional communication in situations that are problematic. The emotional intelligence of the individual is represented in the article as a cognitive ability to perceive and analyze both their own and others’ emotional states and emotional manifestations; as well as the ability to correctly regulate and use them. Communicative tolerance, in turn, is one of the most important features of the police officer, which shows his attitude to people, the degree of tolerance to unpleasant or unacceptable, in his opinion, mental states, qualities and deeds. As a psychodiagnostic tool, the questionnaire “General communicative tolerance” (V. V. Boyko) and the “Emotional Intelligence” test (D. V. Lusin) were used. The sample consisted of 132 students of initial training of police officers. The results of the study indicate differences in the manifestations of emotional intelligence in students with different levels of communicative tolerance. It is empirically proven that emotional intelligence in situations of problematic communication acts as an integral personality of the police officer, which allows him to successfully recognize and interpret the emotions of both his own and the communication partner. The study of the level of emotional intelligence of the police at the stage of professional training will allow the psychological support service to better address the tasks of professional selection and psychological support for future policemen.